The Spatiotemporal Characteristics of Coupling Effect between Roof and Backfill Body in Dense Backfill Mining. (2nd February 2021) - Zhao, Xinyuan; Li, Xinwang; Yang, Ke; Wei, Zhen
Abstract : Backfill mining has become an important part of coal mine green mining technology. In this paper, the spatiotemporal characteristics of coupling effect between the roof and dense backfill body were analyzed by theoretical analysis and similar simulation test, and Xingtai Mine in China was taken as an engineering case for verification. The results show that the larger subsidence of the roof is, the stronger the supporting capacity of the backfill body is, and the interaction between the two is more obvious, thus showing a coupling effect. This coupling effect presents a regular variation with the increase of backfill distance and time, that is, the coupling degree of roof and backfill body is high in the middle of goaf and low in the vicinity of the coal pillar in spatial distribution, and the coupling behavior of roof and backfill body continues to occur slowly with time. Through the monitoring of stress and displacement in the engineering site and the analysis of borehole observation results, the spatiotemporal coupling effect between roof subsidence and backfill support is fully verified. The research results are of great significance to the control of surrounding rock in backfill mining, the study of the mechanical aging characteristics of backfilling materials, and the optimization of backfill body support performance.